2003
DOI: 10.1046/j.1365-2036.2003.01464.x
|View full text |Cite
|
Sign up to set email alerts
|

Esomeprazole 20 mg and lansoprazole 15 mg in maintaining healed reflux oesophagitis: Metropole study results

Abstract: SUMMARY Aim:To compare the efficacy of esomeprazole, 20 mg once daily, vs. lansoprazole, 15 mg once daily, for the maintenance treatment of patients with healed reflux oesophagitis. Methods:During the initial open healing phase, 1391 patients with endoscopically verified reflux oesophagitis and a history of heartburn, with or without acid regurgitation, received esomeprazole 40 mg for 4-8 weeks. Patients who were healed (identified by endoscopy at 4 or 8 weeks) and symptom free were then randomized to receive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(30 citation statements)
references
References 34 publications
1
24
1
4
Order By: Relevance
“…[1][2][3] Esomeprazole 20 mg once daily maintains healing and symptom relief for 6 months in more patients than the FDA-approved maintenance dose of lansoprazole, 15 mg once daily. 4 Esomeprazole is currently available in the USA as a capsule containing enteric-coated pellets. For patients with difficulties swallowing the intact capsule, the pellets within the capsule can be administered mixed in one tablespoonful of apple sauce without affecting drug bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Esomeprazole 20 mg once daily maintains healing and symptom relief for 6 months in more patients than the FDA-approved maintenance dose of lansoprazole, 15 mg once daily. 4 Esomeprazole is currently available in the USA as a capsule containing enteric-coated pellets. For patients with difficulties swallowing the intact capsule, the pellets within the capsule can be administered mixed in one tablespoonful of apple sauce without affecting drug bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…15 One trial demonstrated that low-dose esomeprazole (20 mg) was superior to low-dose lansoprazole (15 mg) in the maintenance of healing of oesophagitis. 27 Low-dose esomeprazole was as effective in the maintenance of oesophagitis healing as standard-dose esomeprazole. 32,33 There were no data comparing oesophagitis healing and/or GERD symptom relief with lower doses of esomeprazole vs. standard doses of any proton pump inhibitor.…”
Section: Resultsmentioning
confidence: 94%
“…In addition, with regard to the maintenance of healing of oesophagitis, a single study of high quality showed better maintenance of healing with low-dose esomeprazole compared with low-dose lansoprazole. 27 These data indicate that esomeprazole is superior to all proton pump inhibitors with which it has been compared in terms of the healing of oesophagitis. One possible explanation for these differences in clinical efficacy is related to differences in pharmacokinetics and pharmacodynamics between the compounds.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…3,5,7 Given the validity of the comparator in our study (esomeprazole), it appears that the generic omeprazole used in our study provides a similar degree of intragastric acid suppression. Esomeprazole 20 mg daily has proven effective for maintenance therapy of erosive GERD, 14,15 for on-demand therapy in non-erosive GERD 25,26 and for prevention of gastroduodenal ulcers in patients with nonsteroidal anti-inflammatory drugs. 27 As other intragastric pH studies and pharmaceutical studies have suggested significant differences between different generic omeprazole products, 17,18 the question remains whether generic omeprazole can provide a similar clinical efficacy as other original PPI brands.…”
Section: Discussionmentioning
confidence: 99%